2022
DOI: 10.1002/ijgo.14233
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy for cervical intraepithelial neoplasia: A retrospective observational multi‐institutional study

Abstract: Objective To analyze the clinical management, the outcomes, and the trend in hysterectomy rates (HR) in patients who underwent this procedure for cervical intraepithelial neoplasia (CIN). Methods Multicentric retrospective observational study conducted on 242 patients who underwent hysterectomy for CIN between 2010 and 2020 in nine Italian institutions. Hysterectomy for invasive or micro‐invasive neoplasia, sub‐total hysterectomy, or trachelectomy were excluded. Results A significant increase in the trend of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
(81 reference statements)
2
10
0
Order By: Relevance
“…Andrea et al reported the development of high-grade VaIN and vaginal cancer in 7 out of 242 cases (2.89%). 7 In our study of 155 patients, this value was 2.6%. Other studies on VaIN recurrence have only focused on the early postoperative period; however, we think that our value is acceptable compared to previous reports.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Andrea et al reported the development of high-grade VaIN and vaginal cancer in 7 out of 242 cases (2.89%). 7 In our study of 155 patients, this value was 2.6%. Other studies on VaIN recurrence have only focused on the early postoperative period; however, we think that our value is acceptable compared to previous reports.…”
Section: Discussionmentioning
confidence: 52%
“…3,4 Therefore, some reports suggest that hysterectomy is recommended for especially elderly CIN3 patients. 5,6 Although hysterectomy is more invasive than conization, 7 clinicians often explain to patients that it is a "definitive" treatment strategy. In other words, clinicians think that the hysterectomy will free the patient from frequent hospital visits without worrying about the possibility of development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations